Promotion of pitting corrosion at hydrogen-enriched α/γ phase boundaries in austenitic stainless steel weld joints. (1st April 2022) - Li, Wenyao; Guo, Tao; Xu, Lining; Chen, Lin; Jiang, Baolong; Wang, Xuehan; Wu, Huanchun; Qiao, Lijie
Abstract: Weld joints can experience numerous defects, which may become enriched in hydrogen and form pits after an attack. However, few in situ studies have been conducted on the relationship between hydrogen enrichment and pitting initiation sites. Moreover, the mechanism by which hydrogen enrichment promotes the initiation and propagation of pitting is unknown. In this study, the pitting susceptibility of austenitic stainless steel weld joints that had been used for 6 years in a hydrocracking unit was investigated. Scanning Kelvin probe force microscopy (SKPFM) was performed to characterize the Volta potential before and after hydrogen removal. The α/γ phase boundaries of the as-received samples were mostly enriched in hydrogen. Furthermore, the α/γ phase boundaries were the preferential locations for the initiation and propagation of pits, which were located at sites of hydrogen enrichment. The results of focused ion beam analysis revealed that the pits deepened along the α/γ phase boundaries and achieved stability. Hydrogen enrichment promotes the transformation of metastable pits to stable pits, which may be the mechanism underlying the promotion of pitting propagation by hydrogen enrichment. Graphical abstract: Image, graphical abstract (a) The Volta potential of α, γ and α/γ phase boundary, (b) SIMS map of hydrogen, SEM high magnification images of pits on (c) the as-received samples and (d) the dehydrogenation samples (baked at 300 °C for 10 h) after immersion test, (e) longitudinal propagation of pits and (f) the pit morphologies in the horizontal direction.